2011
DOI: 10.1007/s10654-011-9590-5
|View full text |Cite
|
Sign up to set email alerts
|

Doubling in the use of thyroid hormone replacement therapy in Denmark: association to iodization of salt?

Abstract: Iodization of salt is an effective strategy to prevent iodine deficiency disorders. Recent studies, however, indicate that increasing the iodine intake in a population may give rise to an increased incidence of hypothyroidism, but the association has not been fully clarified. In Denmark, iodization of salt was initiated in 1998 because of mild-to-moderate iodine deficiency. The aim of this study was to evaluate the effect of the raised iodine intake on the nationwide incident use of thyroid hormone replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Further, this study demonstrated a high risk of overtreatment since 10% had reduced TSH [15]. A register study in Denmark describes an increase of prescriptions of L-T 4 , with an incidence rate increase of 81% over 9 years from 1997 to 2008 [16]. These changes could partly be due to the iodine fortification or a higher diagnostic activity with regard to thyroid dysfunction, but could also be due to an intensified treatment of subclinical hypothyroidism [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further, this study demonstrated a high risk of overtreatment since 10% had reduced TSH [15]. A register study in Denmark describes an increase of prescriptions of L-T 4 , with an incidence rate increase of 81% over 9 years from 1997 to 2008 [16]. These changes could partly be due to the iodine fortification or a higher diagnostic activity with regard to thyroid dysfunction, but could also be due to an intensified treatment of subclinical hypothyroidism [16].…”
Section: Discussionmentioning
confidence: 94%
“…A register study in Denmark describes an increase of prescriptions of L-T 4 , with an incidence rate increase of 81% over 9 years from 1997 to 2008 [16]. These changes could partly be due to the iodine fortification or a higher diagnostic activity with regard to thyroid dysfunction, but could also be due to an intensified treatment of subclinical hypothyroidism [16]. In the context of overtreatment, it was striking that we found 28% of the respondents adjust their medicine themselves (probably due to changes in the pattern of symptoms) and 14% of all respondents reported a suppressed TSH <0.01 mU/l.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, there were approximately 80.000 patients in Denmark treated with levothyroxine [3]. Since GSK had a monopoly position, all these subjects were treated with a GSK product, Eltroxin.…”
Section: Denmarkmentioning
confidence: 99%
“…Thus, the annual number of thyroid hormone prescription items dispensed in England more than doubled from 1998 to 2007 (12), and in the Tayside region in Scotland, the prevalence of treated hypothyroidism increased by 63% from 1994 to 2001 (13). In Denmark, the incidence rate of treated hypothyroidism increased by w80% from 1997 to 2008, which may be explained both by more extensive detection and treatment of hypothyroidism and by an increased incidence of hypothyroidism due to the introduction of iodized salt (14). However, the Norwegian population has long been considered to be iodine sufficient (15), and it seems unlikely that changes in iodine intake may explain the changes that we observed.…”
Section: Huntmentioning
confidence: 99%